2010
DOI: 10.1007/s10147-010-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

O 6-Methylguanine DNA methyltransferase determined by promoter hypermethylation and immunohistochemical expression is correlated with progression-free survival in patients with glioblastoma

Abstract: Low MGMT expression and MGMT promoter methylation are both predictive markers for slower tumor progression in patients with glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 34 publications
5
31
0
2
Order By: Relevance
“…Our data also confirm MGMT methylation as a positive prognostic factor in both IDH1 -mutated and wild-type gliomas (25), with the percentage of MGMT methylation showing a direct correlation with increasing OS (38). Increased OS in patients with MGMT methylation is attributable to a positive response to TMZ, rather than a biological effect on tumor development.…”
Section: Discussionsupporting
confidence: 80%
“…Our data also confirm MGMT methylation as a positive prognostic factor in both IDH1 -mutated and wild-type gliomas (25), with the percentage of MGMT methylation showing a direct correlation with increasing OS (38). Increased OS in patients with MGMT methylation is attributable to a positive response to TMZ, rather than a biological effect on tumor development.…”
Section: Discussionsupporting
confidence: 80%
“…The concept is that silencing of MGMT by promoter methylation is reflected by a loss of MGMT protein expression leading to increased sensitivity of tumours to alkylation-induced DNA damage. However, most studies comparing MGMT promoter methylation analysis with loss of MGMT protein expression as a potential surrogate marker for an inactivation of the MGMT gene described only a poor or lacking correlation [12,13,14,15,16], except for a study by Sonoda et al [17] that reported a good correlation between the two methods.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 For MGMT promoter methylation analysis, we performed methylationspecific PCR. 23,29,30 The chromosome copy numbers of 7p (EGFR), 9p (CDKN2A), and 10q (PTEN) were analyzed by multiplex ligation-dependent probe amplification (MLPA) using the probe mix from the SALSA MLPA Kit P105 Glioma-2 (MRC-Holland), as previously reported. …”
mentioning
confidence: 99%